2018
DOI: 10.1186/s13568-018-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the enzymatic hydrolysis of batch organosolv-pretreated birch and spruce biomass

Abstract: A shift towards a sustainable and green society is vital to reduce the negative effects of climate change associated with increased CO2 emissions. Lignocellulosic biomass is both renewable and abundant, but is recalcitrant to deconstruction. Among the methods of pretreatment available, organosolv (OS) delignifies cellulose efficiently, significantly improving its digestibility by enzymes. We have assessed the hydrolysability of the cellulose-rich solid fractions from OS-pretreated spruce and birch at 2% w/v lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the absence of acid, spruce was treated with 52% v/v ethanol and birch with 60% ethanol and pretreatment took place at 200 °C for 30 min [ 34 ]. Steam explosion pretreatment was performed for 5 min, at 225 °C with H 2 SO 4 0.5% w/w biomass for spruce and at 200 °C with H 2 SO 4 0.14% w/w biomass for birch [ 35 ]. The cellulose, hemicellulose and lignin content of each material are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of acid, spruce was treated with 52% v/v ethanol and birch with 60% ethanol and pretreatment took place at 200 °C for 30 min [ 34 ]. Steam explosion pretreatment was performed for 5 min, at 225 °C with H 2 SO 4 0.5% w/w biomass for spruce and at 200 °C with H 2 SO 4 0.14% w/w biomass for birch [ 35 ]. The cellulose, hemicellulose and lignin content of each material are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the response of the different materials to the pretreatment method that is being used is also distinctive. It has been reported that after the organosolv pretreatment of both birch and spruce biomass the lignin removal is more significant for birch than for spruce and therefore, the enzymatic digestibility showed higher improvement in the case of birch than in the case of spruce [33,34], as it can also be observed by the composition of the OS pretreated substrates that were used for this study.…”
Section: Discussionmentioning
confidence: 57%
“…In this case, the reaction was evaluated until 48 h. Due to the very low enzyme dosage, the hydrolysis rate was lower, and the maximum TY achieved was below that the one obtained with 10 FPU/g DB (49% in contrast with 61%); however, if the analysis is made per unit of enzyme used, we obtained 49% against 6.1% when using 1 or 10 FPU, respectively. Also, OS selectivity decreases slowly in comparison to enzyme hydrolysis with 10 FPU/g DB, reaching 0.5 at 48 h. The differences between TY are not as big as the ones obtained by other authors when increasing the enzyme dosage, for example, [31] tripled the saccharification yield when doubling the enzyme dosage (3 FPU/g) working with pre-treated birch. This very low dosage of ).…”
Section: Enzymatic Hydrolysis Of Pre-treated Bpp With Cellulasementioning
confidence: 65%